Beta-Hydroxybutyrate Alters the mRNA Cytokine Profile from Mouse Macrophages Challenged with Streptococcus uberis - T. H. Swartz; L. K. Mamedova; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to determine if β-hydroxybutyrate (BHB) altered inflammatory responses in macrophages challenged with a common mastitis pathogen,Streptococcus uberis. Mouse macrophages (RAW 264.7 line) were cultured either in the presence or absence of BHB for 24 h, and then challenged or not withS. uberis. Relative transcript abundance of cell membrane receptors (TLR2 and GPR109a), cytokines (IL-1β, IL-10, TNFα, and TGFβ), and chemokines (CXCL2 and CCL5) were determined using quantitative real-time polymerase chain reaction (qPCR) and normalized against the geometric mean of HPRT and B2M.Streptococcus uberisactivated the macrophages, noted by greater transcript abundance of analyzed genes. Intriguingly,S. uberisincreased GPR109a mRNA abundance, a receptor that is activated by BHB. Consequently, BHB dose-dependently increased transcript abundance of the pro-inflammatory cytokine (IL-1β) and the anti-inflammatory cytokine (IL-10) but had no effect on TNFα or TGFβ. Moreover, BHB increased mRNA abundance of the chemokines, CXCL2 and CCL5. These data suggest a dysregulated immune response towardS. uberisdue to BHB treatment, similar to what is seen in transition dairy cows. Future studies should be conducted in vivo to test the effect of BHB on immune function during an intramammary challenge.
Keywords: mastitis; ketosis; inflammation